2021
DOI: 10.1021/acs.inorgchem.1c00278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solution Chemistry on Growth and Structural Features of Mo-Substituted Spinel Iron Oxides

Abstract: The effect of crystallizing solution chemistry on the chemistry of subsequently asgrown materials was investigated for Mo-substituted iron oxides prepared by thermally activated co-precipitation. In the presence of Mo ions, we find that varying the oxidation state of the iron precursor from Fe(II) to Fe(III) causes a progressive loss of atomic long-range order with the stabilization of 2-4 nm particles for the sample prepared with Fe(III). The oxidation state of the Fe precursor also affects the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…34 Moreover, the understanding of the formation mechanism of highly defective compounds could also be considered to better understand how cationic vacancies are involved in the growth of inorganic nanoparticles. 35,36 The use of cationic vacancies has emerged as an effective strategy to improve the electrochemical properties of electrode materials as reviewed by Hahn et al 11 and Gao et al 37 As shown in these reviews, defect engineering has been demonstrated for different charge carriers spanning proton, monovalent, and polyvalent ions. Rationalizing the observed enhanced/modified properties implies that cationic-deficient materials are well described.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Moreover, the understanding of the formation mechanism of highly defective compounds could also be considered to better understand how cationic vacancies are involved in the growth of inorganic nanoparticles. 35,36 The use of cationic vacancies has emerged as an effective strategy to improve the electrochemical properties of electrode materials as reviewed by Hahn et al 11 and Gao et al 37 As shown in these reviews, defect engineering has been demonstrated for different charge carriers spanning proton, monovalent, and polyvalent ions. Rationalizing the observed enhanced/modified properties implies that cationic-deficient materials are well described.…”
Section: Perspectivesmentioning
confidence: 99%
“…Although it is known that certain types of crystal lattices, such as the spinel structure, are naturally prone to accommodating cationic vacancies, further studies may be based on the identification of frameworks capable of hosting a large content of vacancies, a wide range of elements, oxidation states, and, in turn, various phase compositions, i.e., adaptable frameworks . Moreover, the understanding of the formation mechanism of highly defective compounds could also be considered to better understand how cationic vacancies are involved in the growth of inorganic nanoparticles. , …”
Section: Perspectivesmentioning
confidence: 99%
“…The similar energy position of the absorption edge of the Mo‐doped sample with MoO 2 reference confirmed the dominant Mo 4+ valence state in Fe 2.93 ▫ 0.017 Mo 0.053 O 4 . [ 37,49 ] Thus, the lattice enlargement in the Rietveld refinement was undoubtedly explained by the larger Mo 4+ ions (rMo4+=0.79${r_{M{o^{4 + }}}} = 0.79$Å [ 50 ] versus rFe3+=0.65${r_{F{e^{3 + }}}} = 0.65$Å [ 39 ] ). [ 51 ] Moreover, the absence of the pre‐peak indicated that Mo preferred to occupy at the 16 d sites with higher O h symmetries than 8 a sites with T d symmetries, [ 52 ] which was consistent with DFT results.…”
Section: Resultsmentioning
confidence: 99%
“…[35] The creation of chemical defects is mainly dependent on the synthesis method. [36,37] In the present study, we used a simple and economical sol-gel process to develop a novel Mo 4+ -incorporated Fe 3 O 4 with cationic vacancies. Further, we investigated the role of cationic vacancies in the structure and electrochemical properties of molybdenum (Mo)-doped Fe 3 O 4 for LIBs.…”
mentioning
confidence: 99%
“…The code has been used in a number of studies, including some focussed on rationalising the properties of known materials (Squires et al, 2022(Squires et al, , 2021 and others focussed on predicting the properties of novel materials (Jackson et al, 2022). The code can also assist with visualising defect energetics (Haouari et al, 2021).…”
Section: Statement Of Needmentioning
confidence: 99%